Imitation smoke sheet rubber as well as preparation method and application thereof
By flocculating and maturing in natural latex, combined with technical means of hanging sheet drying and imitation smoke coating, imitation smoke sheet rubber with high physical and mechanical properties and ozone resistance is prepared, which solves the problem of insufficient performance of existing natural rubber products and realizes high-performance film preparation suitable for aviation tires and high-performance equipment.
Patent Information
- Application Number
- CN202411861485.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-02-28
AI Technical Summary
Existing natural rubber products have shortcomings in physical and mechanical properties, ozone resistance and fatigue resistance, and it is difficult to meet the requirements of aviation tires and high-performance equipment.
Using a method of preparing a cigarette-imitated sheet glue, natural latex is mixed with alkaline protease or organic acid, flocculation and maturation, and then pressed into film and dried on the sheet. During the drying process, temperature and humidity are controlled to prevent the destruction of rubber molecular chains, and after drying, a smoky coating is applied to inhibit the enzyme's decomposition of non-glue components.
The prepared imitation cigarette sheet glue has high tensile strength, good heat-oxygen aging resistance and long ozone cracking time, which can meet the needs of aviation tires and high-performance equipment. At the same time, the production process is simple, low cost, and environmentally friendly and efficient.
Smart Images

Figure BDA0005193310820000111 
Figure BDA0005193310820000112 
Figure BDA0005193310820000121
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of natural rubber rubber making, and specifically relates to a cigarette-imitation sheet rubber and a preparation method and application thereof. Background Art
[0002] In addition to rubber hydrocarbons and water, natural latex also contains a large amount of non-rubber substances such as proteins, lipids, organic acids and sugars. Since the rubber particles in natural latex are protected by the double electric layer composed of hydrophilic substances such as proteins and lipids, natural latex can maintain a stable colloidal state. When natural latex is contaminated by microorganisms, or when acid, inorganic salts are added, or when heated, frozen, irradiated, etc., natural latex can lose stability and coagulate or gel. At present, the coagulation methods of natural latex are mainly chemical, biological and physical coagulation methods. The chemical method is to add coagulants such as acids, salts, and dehydrating agents to destroy the double electric layer of latex and coagulate; the biological method is to use the original or added microorganisms or enzymes in the latex to destroy the protein in the double electric layer of the latex and coagulate; the physical coagulation method is to use physical methods such as microwave radiation or heating, mechanical stirring to destroy the double electric layer of latex and coagulate natural latex.
[0003] The rubber obtained by natural latex coagulation in the rubber plantation is called rubber plantation gel, which mainly includes rubber cup gel, rubber ball, rubber line, etc. The film obtained by pressing and dehydrating natural latex after artificial coagulation is called raw rubber film. Since rubber plantation gel and raw rubber film often have high impurity content, they need to be fully washed and processed into standard rubber products through processes such as granulation and drying.
[0004] The processing of natural rubber mainly adopts the centralized processing mode, that is, ammonia is added to the fresh latex collected in the rubber plantation as a preservative, and then the latex is transported back to the processing plant for centralized processing. There are three main ways of centralized processing in the factory. The first is to add acid to the fresh latex to neutralize ammonia and use acid to coagulate the latex. The coagulated clots are processed into standard rubber products after pressing, washing, granulation, and drying; the second is to obtain concentrated latex and rubber clear after centrifugal concentration and separation of natural rubber latex, and the concentrated latex becomes concentrated latex products after stabilization and maturation; the third is the production of smoked sheet rubber, which is to transport the latex back to the processing plant for centralized processing, add acid to the fresh latex to neutralize ammonia and use acid to coagulate the latex, and the coagulated clots are pressed, washed, and pressed into sheets, and then hung in the fumigation room, and then smoked and dried at low temperature to a moisture content of 2% to 4% to obtain smoked rubber sheets. Smoked rubber sheets are graded according to the quality standards of smoked rubber sheets.
[0005] At present, the inspection results of standard natural rubber products coagulated by acid using the above method show that the performance of the pure rubber formula of most standard rubber products is a tensile strength of 19.6-20.5MPa, a low resistance to heat and oxygen aging, a tear strength of 22-26kN / m, an ozone cracking resistance of 30-60min, a Mooney viscosity of about 60-70ML(1+4)100℃, an initial plasticity value P0 of 30-40, and a plasticity retention rate of 65%-75%; the performance of the pure rubber formula of the standard rubber produced by most raw films is a tensile strength of 20-22MPa, a low resistance to heat and oxygen aging, an ozone cracking resistance of 30-60min, a Mooney viscosity of about 65-75ML(1+4)100℃, an initial plasticity value P0 of 35-40, and a plasticity retention rate of 70%-80%. However, standard rubber products prepared by existing methods are difficult to use in the production of aviation tires and other natural rubber equipment requiring high physical and mechanical properties, high ozone resistance and high fatigue resistance. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a cigarette-imitation sheet adhesive and a preparation method and application thereof.
[0007] A method for preparing a cigarette-like sheet adhesive comprises the following steps:
[0008] The natural rubber latex is mixed with alkaline protease or organic acid to obtain a flocculent gel, and the flocculent gel is left to mature; wherein the dry rubber content in the natural rubber latex is 20% to 62%, the coagulation concentration of the fresh latex is 20% to 30%, and the ammonia content is less than 0.05%;
[0009] After the floc gel is fully matured, it is pressed into a film, and the film is hung and dried at 15°C to 120°C to obtain a film with a moisture content of 2% to 20%. During film processing, the film is hung and dried, and its purpose is to give a certain stretching force through hanging stretching, which is conducive to the extrusion of water and the formation of a certain micro-orientation.
[0010] The imitation smoke coating is applied on both sides of the dried film to reduce the decomposition of protein and phospholipid, so as to obtain the imitation smoke sheet glue; wherein, the mass of the imitation smoke coating is less than 2% of the mass of the dry glue. Since the moisture content of the film before drying is relatively large, if the imitation smoke coating is applied at this time, as the film is hung and continuously dried, the imitation smoke coating will drip, causing waste; when applying the imitation smoke coating, since spraying requires the use of a thinner liquid, but the thinner liquid cannot reach the required coating amount, the present invention selects a brushing method.
[0011] The imitation smoke coating is prepared from the following components in parts by weight:
[0012] 50-100 parts of oil, 5-50 parts of polyphenols, 5-50 parts of polycyclic aromatic hydrocarbons, and 5-50 parts of sterols. Oil is not only a solvent for coating, but also a carrier of long-chain fatty acids that can promote the formation of induced crystallinity when natural rubber is subjected to force; the role of polyphenols and sterols is to improve the product's resistance to heat and oxygen aging and ozone cracking; the role of polycyclic aromatic hydrocarbons is to inhibit the decomposition of proteins and lipids by various microbial decomposition enzymes during processing and storage, and maintain the high performance of natural rubber. The components of the imitation smoke coating work together to inhibit the decomposition of non-glue components by enzymes during the drying process of the hanging sheet, especially the protective enzymes on proteins and phospholipids, and maintain the ozone resistance and high performance of the imitation smoke sheet glue.
[0013] In the preparation process of the present invention, the nitrogen content and fatty acid content of natural rubber latex are controlled, thereby reducing heat generation and inducing the generation of crystallized combined long-chain fatty acids; in the drying process, the temperature of the hanging sheet drying is controlled, thereby effectively avoiding damage to the rubber molecular chain and protecting the molecular chain, thereby maintaining the heat-oxidative aging resistance and ozone resistance of the imitation cigarette sheet glue; by applying the imitation cigarette component, the decomposition of the enzyme on non-glue components, namely, protein and phospholipids, during the hanging sheet drying process can be further inhibited, thereby further maintaining the ozone resistance and high performance of the imitation cigarette sheet glue.
[0014] In another preferred embodiment, the hanging sheet drying includes 4 stages, as follows:
[0015] In the first stage, the film is preheated at 60°C to 80°C, in the second stage, after the preheating, the film is dried at a constant temperature of 80°C to 120°C, in the third stage, the first speed reduction drying is performed at 60°C to 80°C, and in the fourth stage, the second speed reduction drying is performed at 15°C to 60°C. In the process of hanging film drying, the present invention strictly controls the drying temperature through the humidity in each stage, so that the rubber does not damage the rubber molecular chain and the non-rubber material that protects the molecular chain as much as possible during the drying process.
[0016] In another preferred embodiment, the oil is any one or more of soybean oil, coconut oil, palm oil, peanut oil, sunflower oil, rapeseed oil, and lard;
[0017] The polyphenolic substance is any one or more of cardanol, tea polyphenols, anthocyanidins, and flavanones;
[0018] The polycyclic aromatic hydrocarbons are any one or more of naphthalene, anthracene, phenanthrene, flavonoids, and benzofluorine;
[0019] The sterol substance is any one or more of cholesterol, β-sitosterol, phytosterol, stigmasterol and fungus sterol.
[0020] In another preferred embodiment, when alkaline protease is added, the mass of alkaline protease accounts for 1.5‰ of the mass of dry rubber; when organic acid solution is added, the organic acid is added to make the pH value of natural rubber latex 4.2-4.3.
[0021] In another preferred embodiment, the enzyme activity of the alkaline protease under alkaline conditions is greater than 6000 PPU / g, and the total number of bacteria is less than 10000 / g;
[0022] The mass percentage concentration of the organic acid is 2%; the organic acid is any one or more of formic acid, acetic acid and propionic acid.
[0023] In another preferred embodiment, the moisture content of the film after the hanging film is dried is 2% to 20%.
[0024] In another preferred embodiment, the thickness of the film is 2 mm to 15 mm.
[0025] The second aspect of the present invention provides an imitation cigarette sheet glue, the impurity content of the imitation cigarette sheet glue is below 0.05%, the tensile strength is ≥25MPa, the elongation at break is ≥750%, the initial plasticity value is ≥35, the plasticity retention rate is ≥80%, the Mooney viscosity is 83±10ML(1+4)100℃, the vulcanization time T90 of the pure glue formula is 10min~25min, the heat-oxidation aging resistance retention rate is ≥85%, and the ozone cracking resistance time is 9h~10h.
[0026] The third party of the present invention provides an application of a cigarette-like sheet rubber in the preparation of aviation equipment, wherein the aviation equipment includes aviation tires.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] (1) The production process of the imitation cigarette sheet rubber prepared by the present invention is simple and the production cost is low. Each link adopts the process and method of controlling the minimum damage to the rubber molecular chain. By controlling the nitrogen content and fatty acid content of natural latex, the heat generation is reduced, and the combined long-chain fatty acids that can induce the generation of crystals are also reduced; the hanging sheet is used to restore the broken molecular chains after being washed, broken and torn, and a local molecular chain micro-orientation is formed. The humidity of each stage of the film hanging sheet drying process strictly controls the drying temperature, so that the rubber does not damage the rubber molecular chain and the non-glue substances that protect the molecular chain as much as possible during the drying process. By applying the imitation smoke component, the enzyme decomposition of non-glue components, especially the protective enzyme decomposition of proteins and phospholipids during the hanging sheet drying process is inhibited, and the ozone resistance and high performance of the imitation cigarette sheet rubber are maintained. The imitation cigarette sheet rubber has good quality and high production recovery rate. The production process is green and environmentally friendly, and the production is economical and efficient.
[0029] (2) The imitation cigarette sheet rubber prepared by the preparation method of the present invention has good mechanical properties, suitable curing time, good heat and oxygen aging resistance, and long ozone cracking resistance. Its tensile strength is ≥25MPa, elongation at break is ≥750%, initial plasticity is ≥35, plasticity retention is ≥80%, Mooney viscosity is 83±10ML(1+4)100℃, and the curing time T of the pure rubber formula is 90 The thermal oxygen aging resistance retention rate is ≥85%, and the ozone cracking resistance time is 9h to 10h. DETAILED DESCRIPTION
[0030] The following will be combined with the specific implementation of the present invention to clearly and completely describe the technical solution in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] The methods described in the embodiments of the present invention are conventional methods unless otherwise specified. The materials, reagents, etc. used can be obtained from commercial sources unless otherwise specified.
[0032] The production of smoked sheet rubber is to transport the latex back to the processing plant for centralized processing, add acid to the fresh latex to neutralize ammonia and use acid to coagulate the latex, and the coagulated clots are creped, washed, and pressed into sheets, and then hung in a fumigation room, and smoked and dried at low temperature until the moisture content of the sheet is 2% to 4%, thereby obtaining smoked sheet rubber. Among them, high-quality smoked sheet rubber, such as No. 1 smoked sheet rubber, has the following properties: the tensile strength is 21 to 23 MPa, the tear strength is 25 to 28 kN / m, the heat-oxidation aging resistance is high, the ozone cracking resistance is 180 to 360 min, the Mooney viscosity is about 65 to 75 ML (1 + 4) 100 ° C, the initial plasticity value P0 is between 35 and 45, and the plasticity retention rate is between 75 and 90%. However, the smoked sheet rubber obtained by the above method cannot meet the requirements of aircraft tire rubber and high-performance equipment.
[0033] Current research shows that the properties of natural rubber are affected not only by the molecular structure of rubber hydrocarbons, but also by non-rubber components and processing technology and conditions. The molecular structure of natural rubber includes the molecular weight and molecular weight distribution of rubber hydrocarbon-polyisoprene. Non-rubber components mainly include proteins, lipids, acetone solubles, inorganic salts, etc., and the total amount of non-rubber components is about 3-5%. The processing technology and conditions are the early preservation of fresh latex, including the type and amount of preservatives, coagulation of latex, coagulation method and amount, tableting, dehydration, washing and granulation degree; drying conditions include drying temperature, time and air humidity, flow rate. Among the factors that affect the performance and consistency of rubber, some factors cannot be controlled, such as climate, season, soil, etc.; some factors are mainly difficult to control from the perspective of growth and yield, such as the strain of rubber trees, tapping system, fertilization, etc. The most effective and feasible way to control and obtain high-performance production is to control the processing process.
[0034] In the standard rubber production process of using acid to coagulate fresh latex preserved with ammonia, the residual ammonia and acid will affect the product's resistance to heat and oxygen aging and ozone cracking, and reduce its mechanical properties. Appropriate sheeting, washing, and creping processes can dehydrate and clean impurities and substances such as acid and ammonia, but excessive crushing and tearing in these processes will cause molecular fractures and damage the mechanical properties of the product.
[0035] In the production process of smoked rubber sheets, due to the absence of a crushing process, excessive damage to the structure of natural rubber is avoided, and the structure of the natural rubber molecular chain is kept intact; due to the smoke components in the smoking process, the drying process inhibits the decomposition of proteins and phospholipids by microorganisms, laying the foundation for high performance. The main types of protein in natural rubber are α-globulin, rubber protein, basic protein and fibrous protein. Protein can reduce the activation energy of vulcanization and promote rubber vulcanization; the difference in protein varieties has different effects on vulcanization. At the same time, the binding protein formed by the protein in the form of ω end group on the natural rubber molecular chain can improve the resistance to heat oxygen and ozone aging. However, if there is too much free protein, the vulcanization speed is too fast, which is not conducive to production, and it is easy to grow mold and generate heat; the determination of protein content is calculated by detecting the nitrogen content of amino acids in the protein. Therefore, the appropriate protein type and content can maintain the high performance of natural rubber. In addition, the other end of the natural rubber molecular chain end group is linked to phospholipids. The long-chain fatty acids in phospholipids are the main inducing substances that enable natural rubber to form induced crystallinity when the molecular chain is subjected to strain, and are the key substances to resist strain damage in obtaining high performance. Therefore, in the production process, it is necessary to effectively inhibit the decomposition of long-chain fatty acids in proteins and phospholipids by microorganisms to maintain the high performance of the product.
[0036] Control of the drying process is the key to maintaining heat-oxidative aging resistance and ozone resistance and obtaining high-performance products. Too high a temperature will seriously damage the rubber molecular chains and degrade them, and cause non-rubber substances on the molecular chains to be damaged by heat, thereby reducing the product's mechanical properties, aging properties and ozone resistance. If the temperature is too low and the drying time is too long, it is also prone to mold growth and undercooking. The final moisture content of the product should be controlled within the range of 2% to 4% to avoid over-drying and stickiness.
[0037] The embodiment of the present invention provides a smoke-like rubber sheet and a preparation method and application thereof. The invention selects high-quality natural latex cut normally, adopts a production process and method with minimal damage to rubber molecular chains, controls nitrogen content within a certain range by adopting an organic acid or alkaline protease coagulation method, ensures that the rubber has a suitable non-rubber component content, and ensures that the natural rubber has sufficient aging time after coagulation; fully removes impurities, moisture, residual acid and ammonia during the pressing and washing process, does not need to be torn and granulated, and reduces damage to the molecular chains; utilizes a hanging sheet drying with controllable temperature and humidity to restore the rubber molecular chains that are less broken after washing and pressing, strictly controls the drying temperature, and makes the rubber molecular chains and non-rubber substances that protect the molecular chains as little as possible during the drying process; by applying a smoke-like component, the enzyme decomposition of non-rubber components, especially the protective enzyme decomposition of proteins and phospholipids during the hanging sheet drying process is inhibited, and the ozone resistance and high performance of the product are maintained; the production process is simple, the product quality and consistency are good, the production recovery rate is high, the production process is green and environmentally friendly, and the production is economical and efficient.
[0038] The present invention optimizes the process conditions, such as combining the coagulation system with an organic acid coagulation system or a microbial coagulation system, i.e., alkaline protease, so as to effectively control the nitrogen content of the product, thereby controlling the vulcanization rate, reducing heat generation, and maintaining relatively high resistance to ozone cracking and physical and mechanical properties; by applying the imitation smoke component, the decomposition of proteins and phospholipids by microorganisms in the subsequent drying and storage processes can be effectively inhibited, thereby maintaining the ozone resistance and high mechanical properties of the product, so that the prepared imitation smoke sheet adhesive has good mechanical properties, suitable vulcanization time, good resistance to heat and oxygen aging, and long resistance to ozone cracking.
[0039] The natural rubber used in the embodiments of the present invention includes PRIM600, Reyan 7-33-97, Reyan 879, Reyan 72059, Yunyan 77-4, and PR107 natural rubber strains. The alkaline protease used in the embodiments of the present invention has an enzyme activity greater than 6KPPU / g under alkaline conditions and a total bacterial count less than 10000 / G.
[0040] Example 1
[0041] A method for preparing a cigarette-like sheet adhesive comprises the following steps:
[0042] S1. 1000 kg of fresh PRIM600 natural latex is placed in a mixing tank, wherein the mass percentage of dry rubber in PRIM600 natural latex is 28%, the mass percentage of ammonia is 0.008%, the coagulation concentration of fresh latex is 20%, water is added to adjust the mass percentage of dry rubber to 24%, alkaline protease is added, and the alkaline protease added is 1.5‰ of the mass of dry rubber to control its nitrogen content at 0.10-0.45%, and the coagulation tank is mixed and coagulated evenly for 1 hour to obtain a floc gel, and the floc gel is left to stand for 15 hours to form a coagulum without white water, and the coagulum is pressed and dehydrated, washed, and pressed to form a film with a thickness of 8 mm. The film is hung in a drying cabinet for drying, the hot air temperature at the air inlet is controlled to be 110°C, the air outlet temperature of the drying cabinet is 40°C, and the hanging drying time is 5 days. The film is hung and dried to a moisture content of 2%, and the dried film is obtained.
[0043] S2. The dried film is coated with an imitation smoke coating, and the weight of the imitation smoke coating coated on both sides does not exceed 2% of the total mass of the dry rubber. After coating, the film is preheated at 60° C., and after preheating, it is dried at a constant temperature at 80° C., and then dried at 60° C. for the first time at a reduced speed, and then dried at 15° C. for the second time at a reduced speed, until the moisture content of the film reaches 2% to avoid over-drying and stickiness, thereby obtaining an ozone-resistant high-performance natural rubber product, namely the imitation smoke sheet glue.
[0044] The imitation smoke coating is calculated by weight as follows: 50 parts of oil, 5 parts of polyphenols, 5 parts of polycyclic aromatic hydrocarbons, and 5 parts of sterols. The imitation smoke coating is obtained by weighing the above raw materials according to their weight and then directly mixing them.
[0045] The oil is soybean oil, the polyphenols are cardanol, the polycyclic aromatic hydrocarbons are naphthalene, and the sterols are cholesterol.
[0046] Product quality indicators and performance: impurity content is 0.027%, initial plasticity is 45, plasticity retention rate is 90%, ash content is 0.27%, nitrogen content is 0.39%, Mooney viscosity is 90ML (1+4) 100℃; vulcanization time T of pure rubber formula 90 The test time is 22min, the tensile strength is 28.6MPa, the elongation at break is 860%, the heat generation is 14℃, the thermal oxygen aging resistance retention rate is 75%, and the ozone cracking resistance time is 9.5 hours.
[0047] Example 2
[0048] A method for preparing a cigarette-like sheet adhesive comprises the following steps:
[0049] S1. Put 1000 kg of fresh PR107 natural rubber latex in a mixing tank, wherein the mass percentage of dry rubber in the PR107 natural rubber latex is 28%, the mass percentage of ammonia is 0.15%, and the coagulation concentration of the fresh latex is 25%. Use formic acid with a concentration of 2% determined by calculation, add formic acid to make the pH value of the PR107 natural rubber latex 4.2, so that the PR107 natural rubber latex can be completely coagulated and the complete coagulation time is not less than 1 hour. Mix and coagulate in the coagulation tank for 10 minutes to form flocculation. Wait for the flocculation gel to be completely coagulated and fully matured to obtain a coagulum. Mature for 15 hours to form a coagulum without white water. Press and dehydrate the coagulum, wash, and crepe it into a film with a thickness of 10 mm. Hang the film in a drying cabinet for drying. Control the hot air temperature at the air inlet to be 115° C. and the air outlet temperature at the drying cabinet to be 40° C. The hanging drying time is 6 days. The film is hung and dried to a moisture content of 10% to obtain a dried film.
[0050] S2. Apply an imitation smoke coating to the dried film, the amount of the imitation smoke coating applied on both sides accounts for less than 2% of the total mass of the dry rubber, preheat the film at 70°C after coating, and after preheating, perform constant temperature drying at 100°C, perform a first speed reduction drying at 70°C, and perform a second speed reduction drying at 50°C until the moisture content of the film reaches 3% to avoid over-drying and stickiness, so as to obtain an ozone-resistant high-performance natural rubber product, i.e., the imitation smoke sheet glue.
[0051] The imitation smoke coating is calculated by weight as follows: 60 parts of oil, 10 parts of polyphenols, 10 parts of polycyclic aromatic hydrocarbons, and 10 parts of sterols. The imitation smoke coating is obtained by weighing the above raw materials according to their weight and then directly mixing them.
[0052] The oil is coconut oil, the polyphenols are tea polyphenols, the polycyclic aromatic hydrocarbons are anthracene, and the sterols are β-sitosterol.
[0053] Product quality indicators and performance: impurity content is 0.028%, initial plasticity value P0 is 42, plasticity retention rate PRI is 89%, ash content is 0.27%, nitrogen content is 0.36%, Mooney viscosity is 87ML (1+4) 100℃; vulcanization time T of pure rubber formula 90 The test time is 23min, the tensile strength is 27.8MPa, the elongation at break is 880%, the heat generation is 13℃, the thermal oxygen aging resistance retention rate is 76%, and the ozone cracking resistance time is 10.0 hours.
[0054] Example 3
[0055] A method for preparing a cigarette-like sheet adhesive comprises the following steps:
[0056] S1. Put 1000kg of fresh Yunyan 77-4 natural latex in a mixing tank, wherein the mass percentage of dry rubber in 77-4 natural latex is 28%, the mass percentage of ammonia is 0.005%, the coagulation concentration of fresh latex is 30%, water is added to adjust the mass percentage of dry rubber in coagulated latex concentration to 24%, and alkaline protease is added, and the amount of alkaline protease added is 1.5‰ of the dry rubber content. After the fresh latex is uniformly mixed in the coagulation tank for 1 hour, a flocculent gel is obtained, and the flocculent gel is completely coagulated and fully matured to obtain a coagulum, which is matured for 15 hours to form a coagulum without white water, and the coagulum is pressed, dehydrated, washed, and creped to form a film with a thickness of 9mm; the film is hung in a drying cabinet for drying, the hot air temperature at the air inlet is controlled to be 110℃, the air outlet temperature of the drying cabinet is 40℃, and the hanging drying time is 7 days. The film is hung and dried to a moisture content of 15%, and the dried film is obtained.
[0057] S2. The dried film is coated with an imitation smoke coating, the amount of the imitation smoke coating coated on both sides accounts for less than 2% of the total amount of dry rubber, and the film is preheated at 80°C after coating. After preheating, the film is dried at a constant temperature of 120°C, and a first speed-reduced drying is performed at 80°C, and a second speed-reduced drying is performed at 60°C until the moisture content of the film reaches 4% to avoid excessive drying and stickiness, thereby obtaining an ozone-resistant high-performance natural rubber product, namely the imitation smoke sheet glue.
[0058] The imitation smoke coating comprises, by weight: 80 parts of oil, 30 parts of polyphenols, 30 parts of polycyclic aromatic hydrocarbons, and 30 parts of sterols. The imitation smoke coating is obtained by weighing the above raw materials according to their weight and then directly mixing them.
[0059] The oil is palm oil, the polyphenols are anthocyanins, the polycyclic aromatic hydrocarbons are phenanthrene, and the sterols are phytosterols.
[0060] Product quality indicators and performance: impurity content is 0.042%, initial plasticity is 46, plasticity retention rate is 87%, ash content is 0.15%, nitrogen content is 0.22%, Mooney viscosity is 80ML (1+4) 100℃; vulcanization time T of pure rubber formula 90 The test time is 13min, the tensile strength is 28.0MPa, the elongation at break is 820%, the heat generation is 12℃, the thermal oxygen aging resistance retention rate is 85%, and the ozone cracking resistance time is 9.2 hours.
[0061] Example 4
[0062] A method for preparing a cigarette-like sheet adhesive comprises the following steps:
[0063] S1. Put 1000kg of fresh hot-ground 7-33-97 natural rubber latex in a mixing tank, wherein the mass percentage of dry rubber in 7-33-97 natural rubber latex is 30%, the mass percentage of ammonia is 0.005%, the coagulation concentration of fresh latex is 20%, add water to adjust the mass percentage of dry rubber to 22%, use the formic acid dosage determined by calculation to be 2%, add formic acid to make the pH value 4.3, so that the latex can be completely coagulated and the complete coagulation time is not less than 1 hour. The coagulation tank is mixed and coagulated evenly for 10 minutes to form flocculation, and ripened for 15 hours to form a coagulant without white water. The coagulant is pressed and dehydrated, washed, and creped to form a film with a thickness of 10mm, and the film is hung in a drying cabinet for drying, the hot air temperature at the air inlet is controlled to be 115℃, the air outlet temperature of the drying cabinet is 40℃, and the hanging drying time is 7 days. The film is hung and dried to a moisture content of 20%, and the dried film is obtained.
[0064] S2. The dried rubber sheet is coated with an imitation smoke coating, the amount of the imitation smoke coating coated on both sides accounts for less than 2% of the total mass of the dry rubber, and the film is preheated at 60°C after coating. After preheating, the film is dried at a constant temperature of 80°C, and a first speed-reduced drying is performed at 60°C, and a second speed-reduced drying is performed at 30°C until the moisture content of the film reaches 4% to avoid over-drying and stickiness, so as to obtain an ozone-resistant high-performance natural rubber product, i.e., the imitation smoke sheet rubber.
[0065] The imitation smoke coating is calculated by weight as follows: 100 parts of oil, 50 parts of polyphenols, 50 parts of polycyclic aromatic hydrocarbons, and 50 parts of sterols. The imitation smoke coating is obtained by weighing the above raw materials according to their weight and then directly mixing them.
[0066] The oil is peanut oil, the polyphenols are flavanones, the polycyclic aromatic hydrocarbons are flavonoids, and the sterols are stigmasterol.
[0067] Product quality indicators and performance: impurity content is 0.030%, initial plasticity value P0 is 45, plasticity retention rate PRI is 89%, nitrogen content is 0.25%, ash content is 0.18%, Mooney viscosity is 80ML (1+4) 100℃; vulcanization time T of pure rubber formula 90 The test time is 20min, the tensile strength is 26.5MPa, the elongation at break is 800%, the heat generation is 15℃, the thermal oxygen aging resistance retention rate is 89%, and the ozone cracking resistance time is 9 hours.
[0068] In Tables 1 to 4, 1# smoked sheet rubber is Malaysia No. 1 smoked sheet rubber; Malaysia mark 5 is Malaysia No. 5 standard rubber; Malaysia mark 5L is Malaysia No. 5 latex grade mark; Malaysia mark 5CV is Malaysia No. 5 constant viscosity standard rubber; Malaysia mark 10 is Malaysia No. 10 standard rubber; Malaysia mark 20 is Malaysia No. 20 standard rubber; Malaysia mark 50 is Malaysia No. 50 standard rubber.
[0069] Table 1 Quality indicators of existing rubber
[0070]
[0071] Note: “-” means the substance is not contained.
[0072] Table 2 Performance indicators of existing rubber
[0073]
[0074]
[0075] Since the impurity content of the imitation cigarette sheet rubber prepared in Examples 3 and 4 of the present invention is controlled below 0.05%, the tensile strength is ≥25MPa, the elongation at break is ≥750%, the initial plasticity value is ≥35, the plasticity retention rate is ≥80%, the Mooney viscosity is 83±10ML(1+4)100℃, and the vulcanization time T of the pure rubber formula is 90 The thermal oxygen aging resistance retention rate is ≥85%, and the ozone cracking resistance time is 9 to 10 hours. The following performance tests are carried out taking only Example 1 and Example 2 as examples.
[0076] Table 3 Quality comparison of each sample in the imitation cigarette sheet glue prepared by the present invention and 1# cigarette sheet glue
[0077]
[0078] Table 4 Performance comparison of the imitation cigarette sheet glue prepared by the present invention and 1# cigarette sheet glue
[0079]
[0080]
[0081] From the results in Table 3 and Table 4, the imitation cigarette sheet rubber prepared by the present invention has very good comprehensive performance and can meet the current aviation tires and various equipment requirements with very high performance requirements. The results of the comparison project applied to the imported 1# cigarette rubber sheet commonly used in aviation tire rubber and equipment also have certain advantages in various physical and mechanical properties and processing properties. In particular, the production method for preparing the imitation cigarette sheet rubber provided by the present invention has good consistency of the obtained product, that is, good standard deviation, which is conducive to standardization and engineering.
[0082] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0083] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing an imitation cigarette sheet adhesive, characterized in that: The following steps are involved: The natural latex is mixed with alkaline protease or organic acid solution to obtain a flocculent gel, and the flocculent gel is left to mature; wherein the mass percentage of dry rubber in the natural latex is 20% to 62%, the coagulation concentration of fresh latex is 20% to 30%, and the mass percentage of ammonia is less than 0.05%; The floc gel is left to stand for aging, pressed into a film, and the film is hung for drying at 15°C to 120°C, and a smoke-like coating is applied on both sides of the dried film to reduce the decomposition of protein and phospholipids, thereby obtaining a smoke-like film; wherein the mass of the smoke-like coating is less than 2% of the mass of the dry film; The imitation smoke coating is prepared from the following components in parts by mass: 50 to 100 parts of oils and fats, 5 to 50 parts of polyphenols, 5 to 50 parts of polycyclic aromatic hydrocarbons, and 5 to 50 parts of sterols.
2. The method for preparing the imitation cigarette sheet adhesive according to claim 1, characterized in that: The oil is any one or more of soybean oil, coconut oil, palm oil, peanut oil, sunflower oil, rapeseed oil, and lard; The polyphenolic substance is any one or more of cardanol, tea polyphenols, anthocyanidins, and flavanones; The polycyclic aromatic hydrocarbons are any one or more of naphthalene, anthracene, phenanthrene, flavonoids, and benzofluorine; The sterol substance is any one or more of cholesterol, β-sitosterol, phytosterol, stigmasterol and fungus sterol.
3. The method for preparing the imitation cigarette sheet adhesive according to claim 1, characterized in that: When alkaline protease is added, the mass of alkaline protease accounts for 1.5‰ of the mass of dry rubber; when organic acid solution is added, organic acid is added to make the pH value of natural rubber latex 4.2-4.
3.
4. The method for preparing the imitation cigarette sheet adhesive according to claim 3, characterized in that: The alkaline protease has an enzyme activity of greater than 6000 PPU / g under alkaline conditions and a total bacterial count of less than 10000 / g; The mass percentage concentration of the organic acid solution is 2%; the organic acid is any one or more of formic acid, acetic acid and propionic acid.
5. The method for preparing the imitation cigarette sheet adhesive according to claim 1, characterized in that: The moisture content of the dried film is 2% to 20%.
6. The method for preparing the imitation cigarette sheet adhesive according to claim 1, characterized in that: The thickness of the film is 2 mm to 15 mm.
7. An imitation cigarette sheet adhesive prepared by the method for preparing an imitation cigarette sheet adhesive according to any one of claims 1 to 6, characterized in that: Tensile strength ≥25MPa, elongation at break ≥750%, initial plasticity ≥35, plasticity retention ≥80%, Mooney viscosity 83±10ML(1+4)100℃, vulcanization time T for pure rubber formula 90 The thermal oxygen aging resistance retention rate is ≥85%, and the ozone cracking resistance time is 9h to 10h.
8. Use of the tobacco sheet adhesive according to claim 7 in the preparation of aviation equipment, characterized in that: The aviation equipment includes aviation tires.